A solid acid coated and modified lithium-rich manganese-based positive electrode material and its preparation method and application

Through solid acid coating and modification methods, a composite cladding layer is formed, which solves the performance shortcomings of lithium-rich manganese-based positive electrode materials in voltage attenuation, capacity retention and interface side reaction, and achieves higher electrochemical performance and longer battery life.

CN119764374APending Publication Date: 2025-04-04BEIJING CHUANGNENG HUITONG TECH CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411833449.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have performance shortcomings in terms of fast voltage attenuation, poor capacity retention, structural transformation and interface side reactions, which are difficult to meet the needs of large-scale energy storage and high-energy output of electric vehicles.

Method used

By mixing the lithium-rich manganese-based positive electrode material with solid acid and undergoing solid phase sintering, spinel layer and inorganic salt coating or inorganic salt and C coating layer are formed, the surface structural stability and electrochemical properties of the material are enhanced.

Benefits of technology

The first charge and discharge efficiency and cycle capacity retention rate of lithium-rich manganese-based cathode materials are significantly improved, extending the service life of the battery and improving its energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764374A_ABST
    Figure CN119764374A_ABST
Patent Text Reader

Abstract

The present invention provides a solid acid coated and modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof, belonging to the technical field of lithium ion batteries. The present invention can remove residual alkali on the surface of the lithium-rich manganese-based positive electrode material by solid acid through high temperature, and at the same time, sequentially coat the surface of the lithium-rich manganese-based positive electrode material with a spinel layer and an inorganic salt coating layer or a spinel layer and an inorganic salt and C coating layer, and the composite coating layer is a coating layer of a surface electronic conductor and an ion conductor combination, which can inhibit interface side reactions, reduce the loss of O and transition metals, improve the surface structure stability, effectively improve the first coulomb efficiency of the material, and at the same time prevent the direct contact between the lithium-rich manganese-based positive electrode material and the electrolyte, reduce the side reaction with the electrolyte, and improve the rate performance and cycle stability of the lithium-rich manganese-based positive electrode material, thereby extending the service life of the battery and improving its energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a solid acid coated and modified lithium-rich manganese-based positive electrode material, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in mobile electronic devices, electric vehicles and other fields due to their high energy density and long life. However, existing commercial cathode materials such as LiCoO2, LiFePO4, LiMn2O4, LiNi x Co y Mn 1-x-y Although they perform well in some aspects, they still have some limitations, especially in meeting certain electric vehicle and large-scale energy storage needs. Li-rich manganese-based cathode materials have a higher capacity (about 300 mAh g -1 ) and energy density (approximately 1000Wh kg -1 ) have attracted research attention. These materials have the potential to significantly improve battery performance, especially in applications that require large capacity and high energy output. However, lithium-rich cathode materials face several challenges: fast voltage decay, poor capacity retention, structural transformation, and interfacial side reactions. To address these issues, researchers have tried a variety of methods, including: (1) improving performance by adding a protective layer to the surface of the electrode material. This method is simple, low-cost, and effective, but traditional liquid phase coating technology makes it difficult to form a uniform and dense coating layer; (2) changing the chemical and physical properties of the electrode material by adding other elements; (3) using structural design to change the microstructure of the material to improve its stability and performance. However, the effect of a single doping or surface modification is limited, and it is impossible to take into account the structural and performance decay of lithium-rich manganese-based cathode materials, resulting in performance shortcomings of the material under actual working conditions. Therefore, how to improve the coating effect of the coating layer and thereby improve the electrochemical performance of lithium-rich manganese-based cathode materials has become a technical problem that needs to be solved in this field. Summary of the invention

[0003] The purpose of the present invention is to provide a solid acid coated and modified lithium-rich manganese-based positive electrode material and a preparation method and application thereof. The preparation method provided by the present invention can improve the initial charge and discharge efficiency and cycle capacity retention rate of the lithium-rich manganese-based positive electrode material.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material, comprising the following steps:

[0006] (1) mixing a lithium-rich manganese-based positive electrode material and a solid acid to obtain a mixture; the solid acid comprises any one or more of boric acid, metaboric acid, tetraboric acid, oxalic acid, acetic acid, silicic acid, phytic acid, tartaric acid, benzoic acid, p-hydroxybenzoic acid, citric acid, tannic acid, fumaric acid, phosphoric acid and hypophosphorous acid;

[0007] (2) solid-phase sintering the mixture obtained in step (1) to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

[0008] Preferably, the chemical formula of the lithium-rich manganese-based positive electrode material in step (1) is xLi2MnO3·(1-x)LiMO2, wherein x is 0 to 1.

[0009] Preferably, the particle size of the lithium-rich manganese-based positive electrode material in step (1) is 0.2 to 20 μm.

[0010] Preferably, the mixing method in step (1) is high-speed stirring; the rotation speed of the high-speed stirring is 300 to 6000 r / min, and the time of the high-speed stirring is 10 to 500 min.

[0011] Preferably, the content of solid acid in the mixture of step (1) is 0.01 to 10 wt.%.

[0012] Preferably, in the step (2), the holding temperature of the solid phase sintering is 300-900° C., the holding time of the solid phase sintering is 0.1-12 h, and the heating rate to the solid phase sintering holding temperature is 0.5-10° C. / min.

[0013] The present invention provides a solid acid-coated and modified lithium-rich manganese-based positive electrode material prepared by the preparation method described in the above technical solution.

[0014] Preferably, the solid acid coated and modified lithium-rich manganese-based positive electrode material comprises a lithium-rich manganese-based positive electrode material and a coating layer coated on the surface of the lithium-rich manganese-based positive electrode material, and the thickness of the coating layer is 0.1 to 50 nm.

[0015] Preferably, the coating layer is a spinel layer and an inorganic salt coating layer or a spinel layer and an inorganic salt and a C coating layer.

[0016] The present invention provides the application of the solid acid coated and modified lithium-rich manganese-based positive electrode material described in the above technical solution in a lithium-ion battery.

[0017] The present invention provides a method for preparing a lithium-rich manganese-based positive electrode material coated and modified by a solid acid, comprising the following steps: (1) mixing a lithium-rich manganese-based positive electrode material and a solid acid to obtain a mixture; the solid acid comprises any one or more of boric acid, metaboric acid, tetraboric acid, oxalic acid, acetic acid, silicic acid, phytic acid, tartaric acid, benzoic acid, p-hydroxybenzoic acid, citric acid, tannic acid, fumaric acid, phosphoric acid and hypophosphorous acid; and (2) solid-phase sintering the mixture obtained in step (1) to obtain a lithium-rich manganese-based positive electrode material coated and modified by a solid acid. The present invention mixes a lithium-rich manganese-based positive electrode material and a solid acid, and then performs solid-phase sintering. The solid acid can remove residual alkali on the surface of the lithium-rich manganese-based positive electrode material through high temperature, and at the same time, the surface of the lithium-rich manganese-based positive electrode material is coated with a spinel layer and an inorganic salt coating layer or a spinel layer, an inorganic salt and a C coating layer in sequence. The composite coating layer is a coating layer composed of a surface electronic conductor and an ion conductor, which can inhibit interface side reactions, reduce the loss of O and transition metals, improve the surface structure stability, effectively improve the first coulomb efficiency of the material, and at the same time prevent the direct contact between the lithium-rich manganese-based positive electrode material and the electrolyte, reduce the side reaction with the electrolyte, and improve the rate performance and cycle stability of the lithium-rich manganese-based positive electrode material, thereby extending the service life of the battery and improving its energy density. The preparation method of the present invention is simple and efficient, and the raw materials used are easily available, so it is easier to realize industrialization. The results of the embodiment show that the first charge and discharge efficiency of the button battery prepared with the lithium-rich manganese-based positive electrode material obtained by the preparation method provided by the present invention is greater than 87%, which is much higher than 81.41% of the unmodified lithium-rich manganese-based positive electrode material; after 40 cycles of the button battery, the cycle capacity retention rate reaches more than 96%, which is higher than 92.32% of the unmodified lithium-rich manganese-based positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The first charge and discharge curves of the button batteries prepared in Example 1 and Comparative Example 1 at an operating voltage of 2 to 4.8 V;

[0019] Figure 2 Cycle curves of button batteries prepared in Example 1 and Comparative Example 1 at an operating voltage of 2 to 4.6 V;

[0020] Figure 3 The first charge and discharge curves of the button batteries prepared in Example 2 and Comparative Example 1 at an operating voltage of 2 to 4.8 V;

[0021] Figure 4 Cycle curves of button batteries prepared in Example 2 and Comparative Example 1 at an operating voltage of 2 to 4.6 V. DETAILED DESCRIPTION

[0022] The present invention provides a method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material, comprising the following steps:

[0023] (1) mixing a lithium-rich manganese-based positive electrode material and a solid acid to obtain a mixture;

[0024] (2) solid-phase sintering the mixture obtained in step (1) to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

[0025] Unless otherwise specified in the present invention, the raw materials used are commercially available products well known to those skilled in the art.

[0026] The present invention mixes a lithium-rich manganese-based positive electrode material and a solid acid to obtain a mixture.

[0027] In the present invention, the chemical formula of the lithium-rich manganese-based positive electrode material is preferably xLi2MnO3·(1-x)LiMO2. In the present invention, M is preferably any one or more of Mn, Ni, Al, Co, Fe and Ti, more preferably any one or more of Mn, Ni, Co and Ti, and further preferably Mn and Ni. In the present invention, when the M is Mn and Ni, the molar ratio of Mn to Ni is preferably 1:1. In the present invention, the x is preferably 0 to 1.

[0028] As an embodiment of the present invention, the x may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.

[0029] In the present invention, the particle size of the lithium-rich manganese-based positive electrode material is preferably 0.2-20 μm. The present invention controls the particle size of the lithium-rich manganese-based positive electrode material, which is beneficial to the coating of the solid acid during subsequent mixing.

[0030] As an embodiment of the present invention, the particle size of the lithium-rich manganese-based positive electrode material can be 0.2μm, 0.5μm, 1μm, 2μm, 4μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm or 20μm.

[0031] In the present invention, the solid acid preferably includes any one or more of boric acid, metaboric acid, tetraboric acid, oxalic acid, acetic acid, silicic acid, phytic acid, tartaric acid, benzoic acid, p-hydroxybenzoic acid, citric acid, tannic acid, fumaric acid, phosphoric acid and hypophosphorous acid.

[0032] In the present invention, the mixing method is preferably high-speed stirring; the speed of the high-speed stirring is preferably 300 to 6000 r / min; the time of the high-speed stirring is preferably 10 to 500 min. The present invention can make the raw materials mixed more uniformly by mixing in a high-speed stirring method.

[0033] As an embodiment of the present invention, the rotation speed of the high-speed stirring can be 300r / min, 500r / min, 800r / min, 1000r / min, 1500r / min, 2000r / min, 2500r / min, 3000r / min, 3500r / min, 4000r / min, 4500r / min, 5000r / min, 5500r / min or 6000r / min; the time of the high-speed stirring can be 10min, 30min, 60min, 90min, 120min, 150min, 180min, 210min, 240min, 270min, 300min, 330min, 360min, 390min, 420min, 450min, 480min or 500min.

[0034] In the present invention, the content of the solid acid in the mixture is preferably 0.01-10 wt.%. By controlling the content of the solid acid in the mixture, the thickness of the coating layer formed during subsequent solid phase sintering can be controlled, thereby further improving the electrochemical performance of the lithium-rich manganese-based positive electrode material.

[0035] As an embodiment of the present invention, the content of solid acid in the mixture can be 0.01wt.%, 0.05wt.%, 0.1wt.%, 0.5wt.%, 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.% or 10wt.%.

[0036] After obtaining the mixture, the present invention performs solid phase sintering on the mixture to obtain a solid acid coated and modified lithium-rich manganese-based positive electrode material.

[0037] In the present invention, the holding temperature of the solid phase sintering is preferably 300-900°C; the holding time of the solid phase sintering is preferably 0.1-12h; the heating rate to the holding temperature of the solid phase sintering is preferably 0.5-10°C / min. In the present invention, through solid phase sintering, the solid acid can remove the residual alkali on the surface of the lithium-rich manganese-based positive electrode material at high temperature, and at the same time, the spinel layer and the inorganic salt coating layer or the spinel layer and the inorganic salt and C coating layer are coated on the surface of the lithium-rich manganese-based positive electrode material in sequence, effectively isolating the direct contact between the electrolyte and the active material, significantly improving the interface stability of the material, reducing the side reaction with the electrolyte, thereby extending the service life of the battery and improving its energy density.

[0038] As an embodiment of the present invention, the holding temperature of the solid phase sintering can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C; the holding time of the solid phase sintering can be 0.1h, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h; the heating rate to the solid phase sintering holding temperature can be 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0039] The present invention mixes a lithium-rich manganese-based positive electrode material and a solid acid, and then performs solid-phase sintering. The solid acid can remove residual alkali on the surface of the lithium-rich manganese-based positive electrode material through high temperature, and at the same time, a spinel layer and an inorganic salt coating layer or a spinel layer and an inorganic salt and C coating layer are sequentially coated on the surface of the lithium-rich manganese-based positive electrode material. The composite coating layer is a coating layer composed of a surface electronic conductor and an ion conductor, which can inhibit interface side reactions, reduce the loss of O and transition metals, improve the surface structure stability, effectively improve the first coulomb efficiency of the material, and at the same time prevent the lithium-rich manganese-based positive electrode material from direct contact with an electrolyte, reduce side reactions with the electrolyte, and improve the rate performance and cycle stability of the lithium-rich manganese-based positive electrode material, thereby extending the service life of the battery and improving its energy density.

[0040] The preparation method provided by the invention is simple and efficient, and the raw materials used are easily available, so it is easier to realize industrialization.

[0041] The present invention also provides a solid acid-coated and modified lithium-rich manganese-based positive electrode material prepared by the preparation method described in the above technical solution.

[0042] In the present invention, the solid acid coated and modified lithium-rich manganese-based positive electrode material includes a lithium-rich manganese-based positive electrode material and a coating layer coated on the surface of the lithium-rich manganese-based positive electrode material; the coating layer is preferably a spinel layer and an inorganic salt coating layer or a coated spinel layer and an inorganic salt and C coating layer.

[0043] In the present invention, the thickness of the coating layer is preferably 0.1 to 50 nm.

[0044] As an embodiment of the present invention, the thickness of the coating layer can be 0.1nm, 0.2nm, 0.5nm, 1nm, 2nm, 5nm, 8nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm.

[0045] The present invention also provides the use of the solid acid coated and modified lithium-rich manganese-based positive electrode material described in the above technical solution in a lithium-ion battery.

[0046] The present invention has no special limitation on the specific manner of the application. The solid acid-coated and modified lithium-rich manganese-based positive electrode material can be applied to a lithium-ion battery in a manner well known to those skilled in the art.

[0047] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Example 1

[0049] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0050] (1) mixing a lithium-rich manganese-based positive electrode material and boric acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of boric acid in the mixture is 0.5 wt.%;

[0051] (2) The mixture obtained in step (1) is heated to 500° C. at a rate of 5° C. / min in air and kept at this temperature for 5 h, and then cooled to room temperature to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

[0052] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 1 is a lithium-boron compound and a lithium-rich manganese-based layered oxide coated on the surface of spinel.

[0053] Example 2

[0054] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0055] (1) mixing a lithium-rich manganese-based positive electrode material, boric acid and tannic acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of boric acid in the mixture is 0.25wt.%, and the content of tannic acid is 0.25wt.%;

[0056] (2) The mixture obtained in step (1) is heated to 500° C. at a rate of 5° C. / min in an argon atmosphere and kept at this temperature for 0.5 h. After cooling to room temperature, a solid acid-coated and modified lithium-rich manganese-based positive electrode material is obtained.

[0057] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 2 is a lithium-rich manganese-based layered oxide coated with a lithium-boron compound and carbon and a spinel surface.

[0058] Example 3

[0059] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0060] (1) mixing a lithium-rich manganese-based positive electrode material and silicic acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of silicic acid in the mixture is 1 wt.%;

[0061] (2) The mixture obtained in step (1) is heated to 500° C. at a rate of 5° C. / min in air and kept at this temperature for 0.5 h, and then cooled to room temperature to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

[0062] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 3 is a lithium-silicon compound and a lithium-rich manganese-based layered oxide coated on the surface of spinel.

[0063] Example 4

[0064] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0065] (1) mixing a lithium-rich manganese-based positive electrode material and benzoic acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of benzoic acid in the mixture is 0.5 wt.%;

[0066] (2) The mixture obtained in step (1) is heated to 500° C. at a rate of 2.5° C. / min in air and kept at this temperature for 3 h, and then cooled to room temperature to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

[0067] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 4 is a lithium-rich manganese-based layered oxide coated with a spinel surface.

[0068] Example 5

[0069] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0070] (1) mixing a lithium-rich manganese-based positive electrode material and tannic acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of tannic acid in the mixture is 0.25 wt.%;

[0071] (2) The mixture obtained in step (1) is heated to 500° C. at a rate of 5° C. / min in air and kept at this temperature for 2 h, and then cooled to room temperature to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

[0072] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 5 is a lithium-rich manganese-based layered oxide coated with a spinel surface.

[0073] Example 6

[0074] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0075] (1) mixing a lithium-rich manganese-based positive electrode material and phosphoric acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of phosphoric acid in the mixture is 0.5 wt.%;

[0076] (2) The mixture obtained in step (1) is heated to 400° C. at a rate of 4° C. / min in air and kept at that temperature for 5 h, and then cooled to room temperature to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

[0077] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 6 is a lithium-phosphorus compound and a lithium-rich manganese-based layered oxide coated on the surface of spinel.

[0078] Example 7

[0079] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0080] (1) mixing a lithium-rich manganese-based positive electrode material and hypophosphorous acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of hypophosphorous acid in the mixture is 0.8 wt.%;

[0081] (2) The mixture obtained in step (1) is heated to 500° C. at a rate of 3° C. / min in air and kept at this temperature for 4 h, and then cooled to room temperature to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

[0082] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 7 is a lithium-phosphorus compound and a lithium-rich manganese-based layered oxide coated on the surface of spinel.

[0083] Example 8

[0084] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0085] (1) mixing a lithium-rich manganese-based positive electrode material, boric acid and silicic acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of boric acid in the mixture is 0.25wt.%, and the content of silicic acid is 0.25wt.%;

[0086] (2) The mixture obtained in step (1) is heated to 500° C. at a rate of 5° C. / min in air and kept at this temperature for 0.5 h, and then cooled to room temperature to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

[0087] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 8 is a lithium-silicon and lithium-boron composite compound and a lithium-rich manganese-based layered oxide coated on the spinel surface.

[0088] Example 9

[0089] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0090] (1) mixing a lithium-rich manganese-based positive electrode material, boric acid and tartaric acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of boric acid in the mixture is 0.25wt.%, and the content of tartaric acid is 0.25wt.%;

[0091] (2) The mixture obtained in step (1) is heated to 500° C. at a rate of 5° C. / min in an argon atmosphere and kept at this temperature for 0.5 h. After cooling to room temperature, a solid acid-coated and modified lithium-rich manganese-based positive electrode material is obtained.

[0092] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 9 is a lithium-rich manganese-based layered oxide coated with a lithium-boron compound and carbon and a spinel surface.

[0093] Example 10

[0094] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0095] (1) mixing a lithium-rich manganese-based positive electrode material, tetraboric acid and citric acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of tetraboric acid in the mixture is 0.25wt.%, and the content of citric acid is 0.25wt.%;

[0096] (2) The mixture obtained in step (1) is heated to 400° C. at a rate of 5° C. / min in an argon atmosphere and kept at this temperature for 2 h, and then cooled to room temperature to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

[0097] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 10 is a lithium-rich manganese-based layered oxide coated with a lithium-boron compound and carbon and a spinel surface.

[0098] Embodiment 11

[0099] A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0100] (1) mixing a lithium-rich manganese-based positive electrode material, silicic acid and tannic acid at 2000 r / min for 60 min to obtain a mixture; the chemical formula of the lithium-rich manganese-based positive electrode material is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of the lithium-rich manganese-based positive electrode material is 10 μm; the content of silicic acid in the mixture is 0.25wt.%, and the content of tannic acid is 0.25wt.%;

[0101] (2) The mixture obtained in step (1) is heated to 500° C. at a rate of 5° C. / min in an argon atmosphere and kept at this temperature for 0.5 h. After cooling to room temperature, a solid acid-coated and modified lithium-rich manganese-based positive electrode material is obtained.

[0102] The solid acid coated and modified lithium-rich manganese-based positive electrode material obtained in Example 11 is a lithium-rich manganese-based layered oxide coated with a lithium silicon compound and carbon and spinel surface.

[0103] Comparative Example 1

[0104] Lithium-rich manganese-based positive electrode material, the chemical formula is 0.3Li2MnO30.7LiNi 0.5 Mn 0.5 O2, the particle size of lithium-rich manganese-based positive electrode material is 10μm.

[0105] According to the national standard GB / T41704-2022 "Determination of magnetic foreign matter content and residual alkali content of lithium ion positive electrode material detection method", the surface lithium residue and pH value of the solid acid coated and modified lithium-rich manganese-based positive electrode material provided in Examples 1 to 2 and the lithium-rich manganese-based positive electrode material of Comparative Example 1 were detected, and the results obtained are shown in Table 1:

[0106] Table 1 Surface lithium residues and pH values ​​of the solid acid coated and modified lithium-rich manganese-based positive electrode materials provided in Examples 1 to 2 and the lithium-rich manganese-based positive electrode material of Comparative Example 1

[0107] <![CDATA[Li2CO3(ppm)]]> LiOH(ppm) pH Comparative Example 1 3465 1316 11.78 Example 1 743 128 11.3 Example 2 793 120 11.34

[0108] It can be seen from Table 1 that after surface solid acid treatment, the lithium content of lithium carbonate and lithium hydroxide on the surface of the surface modified lithium-rich manganese-based positive electrode materials obtained in Example 1 and Example 2 is significantly lower than that of the lithium-rich manganese-based positive electrode material in Comparative Example 1, and the alkalinity is weakened, indicating that the preparation method provided by the present invention can not only reduce the content of residual alkali on the surface of the positive electrode material, thereby reducing the risk of interfacial side reactions, reducing gas production, and improving processing performance, which is beneficial to the improvement of electrochemical performance.

[0109] The electrochemical properties of the solid acid coated and modified lithium-rich manganese-based positive electrode materials of Examples 1 to 2 and the lithium-rich manganese-based positive electrode material of Comparative Example 1 were tested, and the test method was:

[0110] 1) 0.27 g of positive electrode material (the solid acid coated and modified lithium-rich manganese-based positive electrode material provided in Examples 1 to 2 and the lithium-rich manganese-based positive electrode material of Comparative Example 1 were tested as positive electrode materials respectively), 0.15 g of conductive carbon black (Kejing), 0.15 g of polyvinylidene fluoride (Alfa) and N-methylpyrrolidone solvent (Aladdin reagent) were mixed, and the solid content after mixing was controlled to be 50%. After mixing evenly with a thinky mixer, the mixture was coated on a 17 μm aluminum foil with a scraper to obtain a pole piece with a coating thickness of 300 μm. The mixture was dried in an oven at 120° C. for 2 h, the pole piece was rolled, and the button cell was assembled to obtain an assembled button cell;

[0111] 2) The assembled button battery obtained in step 1) was subjected to a charge and discharge test on a Xinwei charge and discharge tester at room temperature of 25°C. The first cycle was charged and discharged at a current density of 20 mA / g in a voltage range of 2.0 to 4.8 V, and then the charge and discharge cycle test was performed at a current density of 200 mA / g in a voltage range of 2.0 to 4.6 V. The results were as follows: Figures 1 to 4 shown.

[0112] Depend on Figure 1 It can be seen that after the lithium-rich manganese-based positive electrode material is modified by the preparation method provided by the present invention, the first charge and discharge efficiency of the button battery prepared by the solid acid coated and modified lithium-rich manganese-based positive electrode material provided in Example 1 reaches 89.04%, which is much higher than 81.41% of the unmodified lithium-rich manganese-based positive electrode material.

[0113] Depend on Figure 2 It can be seen that, compared with the unmodified lithium-rich manganese-based positive electrode material (Comparative Example 1), the button battery prepared with the solid acid coated and modified lithium-rich manganese-based positive electrode material provided in Example 1 of the present invention has a cycle capacity retention rate increased from 92.32% to 96.3% after 40 cycles.

[0114] Depend on Figure 3 It can be seen that after the lithium-rich manganese-based positive electrode material is modified by the preparation method provided by the present invention, the first charge and discharge efficiency of the button battery prepared by the solid acid coated and modified lithium-rich manganese-based positive electrode material provided in Example 2 reaches 87.09%, which is much higher than 81.41% of the unmodified lithium-rich manganese-based positive electrode material.

[0115] Depend on Figure 4 It can be seen that, compared with the unmodified lithium-rich manganese-based positive electrode material (Comparative Example 1), the button battery prepared with the solid acid coated and modified lithium-rich manganese-based positive electrode material provided in Example 2 of the present invention has a cycle capacity retention rate increased from 92.32% to 97.06% after 40 cycles.

[0116] Depend on Figures 1 to 4It can be seen that after the lithium-rich manganese-based positive electrode material is modified by the preparation method provided by the present invention, the voltage attenuation, capacity retention rate and rate performance of the lithium-rich manganese-based positive electrode material can be effectively improved.

[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a solid acid coated and modified lithium-rich manganese-based positive electrode material, comprising the following steps: (1) mixing a lithium-rich manganese-based positive electrode material and a solid acid to obtain a mixture; the solid acid comprises any one or more of boric acid, metaboric acid, tetraboric acid, oxalic acid, acetic acid, silicic acid, phytic acid, tartaric acid, benzoic acid, p-hydroxybenzoic acid, citric acid, tannic acid, fumaric acid, phosphoric acid and hypophosphorous acid; (2) solid-phase sintering the mixture obtained in step (1) to obtain a solid acid-coated and modified lithium-rich manganese-based positive electrode material.

2. The preparation method according to claim 1, characterized in that: The chemical formula of the lithium-rich manganese-based positive electrode material in step (1) is xLi2MnO3·(1-x)LiMO2, wherein x is 0 to 1.

3. The preparation method according to claim 1 or 2, characterized in that: The particle size of the lithium-rich manganese-based positive electrode material in step (1) is 0.2 to 20 μm.

4. The preparation method according to claim 1, characterized in that: The mixing method in step (1) is high-speed stirring; the rotation speed of the high-speed stirring is 300 to 6000 r / min, and the time of the high-speed stirring is 10 to 500 min.

5. The preparation method according to claim 1, characterized in that: The content of solid acid in the mixture of step (1) is 0.01 to 10 wt.%.

6. The preparation method according to claim 1, characterized in that: In the step (2), the holding temperature of the solid phase sintering is 300-900° C., the holding time of the solid phase sintering is 0.1-12 hours, and the heating rate to the solid phase sintering holding temperature is 0.5-10° C. / min.

7. The solid acid coated and modified lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 1 to 6.

8. The solid acid coated and modified lithium-rich manganese-based positive electrode material according to claim 7, characterized in that: The solid acid coated and modified lithium-rich manganese-based positive electrode material comprises a lithium-rich manganese-based positive electrode material and a coating layer coated on the surface of the lithium-rich manganese-based positive electrode material, and the thickness of the coating layer is 0.1 to 50 nm.

9. The solid acid coated and modified lithium-rich manganese-based positive electrode material according to claim 8, characterized in that: The coating layer is a spinel layer and an inorganic salt coating layer or a coated spinel layer and an inorganic salt and C coating layer.

10. Use of the solid acid coated and modified lithium-rich manganese-based positive electrode material according to any one of claims 7 to 9 in lithium-ion batteries.

Citation Information

Cited By

  • Sodium-ion battery positive electrode material, modification method, sodium-ion battery and application

    CN120348982A

  • Method for modifying lithium-rich manganese-based positive electrode material, modified lithium-rich manganese-based positive electrode material and battery

    CN122809543A